Pengaruh Latihan Imagery dan Konsentrasi terhadap Ketepatan Tusukan dalam Olahraga Anggar - Prakosa, Muhammad Wahyu Bagus; Hariyanto, Agus; Ismalasari, Rini (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2021)
The purpose of this study is to analyze the effect of imagery and concentration training on puncture accuracy in fencing. It was a quasi-experimental research with a pretest-posttest control group design, involving 15 members of fencing extracurricular club in SMA Muhammadiyah 3 Surabaya. Respondents were then divided into three groups which consisted of 5 people each, which were control group (C), imagery-training group (IM),and concentration-training group (CT). Respondents in IM and CT were assigned to respected training that was conducted for six weeks, and puncture accuracy was measured using kuhadja or fencing skill test before and after 6-weeks of training. The puncture accuracy score was then statistically analyzed using paired t-test and one-way Anova at confidence level set as 95%. Paired t-test analysis found that the mean puncture accuracy score in treatment groups (IM and CT) were higher than the control group, with significance value were 0.013 and 0.000, respectively. Further analysis using Anova test showed that the type of training significantly gave different effect on the pucture accuracy (p <0.05). From these results we can conclude that the imagery and concentration training are proven to be effective in improving student's ability to perform accurate and precise punctures in fencing.